Problem Gambling and Intimate Partner Violence: A Systematic Review and Meta-Analysis. (January 2016) - Dowling, Nicki; Suomi, Aino; Jackson, Alun; Lavis, Tiffany; Patford, Janet; Cockman, Suzanne; Thomas, Shane; Bellringer, Maria; Koziol-Mclain, Jane; Battersby, Malcolm; Harvey, Peter; Abbott, Max
This study provides a systematic review of the empirical evidence related to the association between problem gambling and intimate partner violence (IPV). We identified 14 available studies in the systematic search (8 for victimisation only, 4 for perpetration only and 2 for both victimisation and perpetration). Although there were some equivocal findings, we found that most of the available research suggests that there is a significant relationship between problem gambling and being a victim of IPV. There was more consistent evidence that there is a significant relationship between problem gambling and perpetration of IPV. Meta-analyses revealed that over one third of problem gamblers report being victims of physical IPV (38.1%) or perpetrators of physical IPV (36.5%) and that the prevalence of problem gambling in IPV perpetrators is 11.3%. Although the exact nature of the relationships between problem gambling and IPV is yet to be determined, the findings suggest that less than full employment and clinical anger problems are implicated in the relationship between problem gambling and IPV victimization and that younger age, less than full employment, clinical anger problems, impulsivity, and alcohol and substance use are implicated in the relationship between problem gambling and IPV perpetration. The findings highlight the need for treatment services to undertake routine screening and assessment of problem gambling, IPV, alcohol and substance use problems, and mental health issues and provide interventions designed to manage this cluster of comorbid conditions. Further research is also required to investigate the relationship between problem gambling and violence that extends into the family beyond intimate partners.